2014
DOI: 10.1103/physrevlett.113.247004
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Josephson Vortices on the Surface SuperconductorSi(111)(7×3)

Abstract: We have studied the superconducting Si(111)-( √ 7 × √ 3)-In surface using a 3 He-based lowtemperature scanning tunneling microscope (STM). Zero-bias conductance (ZBC) images taken over a large surface area reveal that vortices are trapped at atomic steps after magnetic fields are applied. The crossover behavior from Pearl to Josephson vortices is clearly identified from their elongated shapes along the steps and significant recovery of superconductivity within the cores. Our numerical calculations combined wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 35 publications
3
57
0
1
Order By: Relevance
“…Among these reconstructions, the √7 × √3 has attracted much interest recently, because it shows a free-electron-like two dimensional metallic state [12,13] and superconductivity at about 3 K [14][15][16][17][18]. It is reported that two phases of the √7 × √3 reconstruction exist, which show slightly different appearances in scanning tunneling microscopy (STM) images, from which they derive their names: a hexagonal and a rectangular phase (denoted as "hex" and "rect", hereafter).…”
Section: Introductionmentioning
confidence: 99%
“…Among these reconstructions, the √7 × √3 has attracted much interest recently, because it shows a free-electron-like two dimensional metallic state [12,13] and superconductivity at about 3 K [14][15][16][17][18]. It is reported that two phases of the √7 × √3 reconstruction exist, which show slightly different appearances in scanning tunneling microscopy (STM) images, from which they derive their names: a hexagonal and a rectangular phase (denoted as "hex" and "rect", hereafter).…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that the atomic steps work as Josephson junctions and allow supercurrents to flow with a limited rate. Detailed results, discussions and theoretical calculations are presented elsewhere [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, impurities locally suppress superconductivity, which in superconducting nanowires can promote a phase slip center, giving rise to the broad temperature transition and residual resistance 25,26 . Very recently, a step in atomically thin films was found to have a strong effect on electronic transport 27,28 and vortex matter 24,29,30 , as a new paradigm in the interplay between the local defects and low-dimensional superconductivity. As an extended defect, the step does not only scatter electrons (leading to the modification on the overall electronic structure of the sample 31 ), but also affects the flow of superconduct-ing currents and the proximity-induced superconducting correlations 27,28 .…”
Section: Introductionmentioning
confidence: 99%